Plasma-aided surface technology for modification of materials referred to fire protection - Dineff, P.; Gospodinova, D.; Kostova, L.; Vladkova, T.; Chen, E. (Вопросы атомной науки и техники, 2008)
There has been considerable interest in dielectric barrier air discharge at atmospheric pressure and room temperature over the past decade due to the increased number of industrial applications. New plasma-aided capillary impregnation technology for flame spreading stop and fire protection of porous materials was developed. Research, based on thermogravimetric analysis (TGA), differential thermal analysis (DTA), and differential scanning calorimetry (DSC), proves that plasma-chemical surface pre-treatment exert material change on chemical interaction between phosphorus containing flame retardant and wood matrix (Pinus sylvestris, Bulgaria; Pseudotsuga, Canada).